Regulatory Oversight, Firm Characteristics, and Audit Quality: Evidence From Indonesia’s Post Pandemic Energy Sector - Estri, Siwi Rawidya; Rofiqoh, Ifah (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
Regulatory transformation and increasing reporting complexity in Indonesia’s post pandemic energy sector highlight the need for a clearer understanding of the factors that influence audit quality. Previous studies report inconsistent findings regarding the effects of audit tenure, audit rotation, firm size, and the audit committee’s effectiveness, raising the question of whether auditor characteristics or client characteristics play a more dominant role. This study aims to examine the effects of audit tenure, audit rotation, and firm size on audit quality and to evaluate whether the audit committee moderates these relationships in energy companies listed on the Indonesia Stock Exchange. A quantitative approach was employed using purposive sampling, resulting in 46 sample firms observed from 2021 to 2024. Logistic regression was used to analyze audit quality proxied by audit opinion. The results show that audit tenure and audit rotation have no significant effect on audit quality, while firm size exhibits a strong and significant positive effect. Moreover, the audit committee does not moderate the relationship between the independent variables and audit quality. These findings indicate that in a strengthened regulatory environment characterized by intensified OJK oversight and consistent SPAP enforcement client characteristics, particularly firm size, play a more decisive role in determining audit quality than auditor characteristics. Theoretically, this study refines agency theory within mature regulatory settings, and practically, it offers guidance for auditor oversight policies, and corporate governance enhancement in the energy sector.